Cultured proteins: An analysis of the policy and regulatory environment in selected geographies - Kreis, Katharine; Zobrist, Stephanie; Parker, Megan E.; Kinderknecht, Kelsey; Perez, Nicostrato D.; Ringler, Claudia (PATH, 2019)
The global burden of malnutrition is unacceptably high. Animal-source foods are important components of diverse diets and provide high-quality proteins and other essential nutrients that promote optimal growth and development. The global demand for animal-source foods is projected to increase substantially, particularly in many low- and lower-middle income countries (LMICs). However, cost is a significant barrier to access and meeting this growing demand through livestock production will be highly resource intensive. As such, sustainable, high-quality alternatives to protein from livestock have the potential for significant transformative impact for both people and the planet. Through a process known as fermentation-based cellular agriculture, animal proteins found in milk and eggs can be produced without animals. According to this method, a gene encoded with an animal protein is introduced into a starter culture of microflora (e.g., fungi or yeast). This culture is grown in controlled fermentation tanks, where it expresses the desired protein. Finally, the protein is separated from the microflora, generally producing a purified protein powder. These resulting “cultured” proteins are designed to be identical to the corresponding animal-source proteins produced through traditional livestock farming and can be used as ingredients in existing or new food products. Although there are many potential sustainability and nutritionrelated benefits of these innovations, they also face several challenges to commercialization and market uptake. This report assesses the current policy and regulatory environment for cultured proteins and their potential applicability in LMIC settings. Specifically, this report focuses on geographies where cultured proteins may be produced, procured, and/or consumed: the United States, the European Union, and two select LMICs (Ethiopia and India).